PERAN GURU DALAM PENINGKATAN LITERASI MELALUI POJOK BACA DI MI NEGERI 1 BANJARNEGARA - Mikyal Hardiyati; Tri Wibowo (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
This research aims to describe the role of teachers in increasing student literacy through reading corners. The research method used is field research with a qualitative descriptive approach. Data collection techniques use observation, interviews and documentation. The data analysis technique uses the Miles and Huberman model which consists of data reduction, data presentation and conclusions. Based on the research results, it shows that literacy has increased through reading corners at MI Negeri 1 Banjarnegara as evidenced by the availability of reading corners in all classrooms and a complete collection of non-study books. Increasing literacy requires the role of teachers. The teacher has a facilitator role in that the teacher provides a representative and comfortable class so that students are able to grow their literacy skills. Teachers are also motivators and inspirers for students, in the sense that through reading corner activities teachers participate in assisting students in improving literacy. Through the reading corner, students are expected to improve their reading skills so that they have insightful knowledge and can easily access information.